2015
DOI: 10.2174/1574891x10666150410130425
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and Occupational Aspects of Leptospirosis in the Coffee-Triangle Region of Colombia, 2007-2011

Abstract: one of the 53 municipalities contributed with almost a quarter of the cases. Agriculture was significantly associated with the incidence. Use of GIS-based epidemiological maps allow to focus actions in prevention and control for risk zones for leptospirosis which still represents a significant issue in the region and Colombia, particularly in agriculture workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Most spatial studies (96.55%, n = 56/58) produced human infection maps and most (73.21%, n = 41/56) utilized data obtained from the national disease surveillance notification systems. Maps were produced to depict incidence or prevalence in certain administrative areas (48.21%, n = 27/56) (Schneider et al, ), national ( n = 11) (Gonwong et al, ; Jansen et al, ; Lau, Clements, et al, ; Massenet, Yvon, Couteaux, & Goarant, ; Robertson et al, ; Rood et al, ; Schneider et al, ; Shi, Tu, & Li, ; Stevens, Carter, Kiep, Stevenson, & Schneeweiss, ; van Alphen et al, ; Zhao et al, ) or sub‐national scales ( n = 15) (Barcellos, Lammerhirt, de Almeida, & dos Santos, ; Barcellos & Sabroza, ; Chaiblich, Lima, Oliveira, Monken, & Penna, ; Garcia‐Ramirez et al, ; Gracie et al, ; Herbreteau et al, ; Ko, Reis, et al, ; Lau, Skelly, Dohnt, & Smythe, ; Mišić‐Majerus, ; Mohammadinia, Alimohammadi, & Saeidian, ; Mohd Radi et al, ; Myint et al, ; Schneider et al, ; Soares et al, ; Vega‐Corredor & Opadeyi, ). Twelve studies used Kernel density estimation technique (Chaiblich et al, ; Cook et al, ; de Melo et al, ; Deshmukh et al, ; Filho et al, ; Lau, Dobson, et al, .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most spatial studies (96.55%, n = 56/58) produced human infection maps and most (73.21%, n = 41/56) utilized data obtained from the national disease surveillance notification systems. Maps were produced to depict incidence or prevalence in certain administrative areas (48.21%, n = 27/56) (Schneider et al, ), national ( n = 11) (Gonwong et al, ; Jansen et al, ; Lau, Clements, et al, ; Massenet, Yvon, Couteaux, & Goarant, ; Robertson et al, ; Rood et al, ; Schneider et al, ; Shi, Tu, & Li, ; Stevens, Carter, Kiep, Stevenson, & Schneeweiss, ; van Alphen et al, ; Zhao et al, ) or sub‐national scales ( n = 15) (Barcellos, Lammerhirt, de Almeida, & dos Santos, ; Barcellos & Sabroza, ; Chaiblich, Lima, Oliveira, Monken, & Penna, ; Garcia‐Ramirez et al, ; Gracie et al, ; Herbreteau et al, ; Ko, Reis, et al, ; Lau, Skelly, Dohnt, & Smythe, ; Mišić‐Majerus, ; Mohammadinia, Alimohammadi, & Saeidian, ; Mohd Radi et al, ; Myint et al, ; Schneider et al, ; Soares et al, ; Vega‐Corredor & Opadeyi, ). Twelve studies used Kernel density estimation technique (Chaiblich et al, ; Cook et al, ; de Melo et al, ; Deshmukh et al, ; Filho et al, ; Lau, Dobson, et al, .…”
Section: Resultsmentioning
confidence: 99%
“…No serogroup or serovar distribution maps at regional and global scale were reported. Spatial and temporal maps were created (21.42%, n = 12/56) (Baquero & Machado, ; Garcia‐Ramirez et al, ; Gracie et al, ; Hagan et al, ; Lau et al, ; Robertson et al, ; Soares et al, ; Sulistyawati, Nirmalawati, & Mardenta, ; Suwanpakdee et al, ; Tassinari et al, ; van Alphen et al, ) to illustrate changes in distribution (Della Rossa et al, ; Gracie et al, ; Lau et al, ; Schneider et al, ; Soares et al, ; Sulistyawati et al, ; Suwanpakdee et al, ; Tassinari et al, ) or disease rates/risks (Baquero & Machado, ; Garcia‐Ramirez et al, ; Hagan et al, ; Robertson et al, ; Suwanpakdee et al, ; van Alphen et al, ) or burden in terms of disability‐adjusted life‐years (DALYs) (Dhewantara et al, ). One set of subnational spatial and temporal maps describing changes in serovar‐specific cases was produced at state level in Australia (Lau et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This study has confirmed that the occurrence of leptospirosis is mainly distributed in middle age group (30 ≤ age < 75). Occupational exposure is a significant risk factor in many countries and is particularly associated with agriculture and animal workers (Garcã­a‐Ramã­rez et al, ). In the present study, most leptospirosis cases typically occurred among farmers, students, rural labourers and the unemployed people.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of leptospirosis cases is known to be uneven and regions of highest incidence have been identified in a number of contexts. 23 , 57 , 87 93 These efforts of leptospirosis mapping were also used to identify spatially associated risk factors. 94 99 This geographical approach of risk mapping or risk identification through spatial analysis will most probably increase in the future and in turn help identify overlooked factors impacting leptospirosis incidence.…”
Section: Leptospirosis: a Public Health Challengementioning
confidence: 99%